1985
DOI: 10.1159/000465722
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heparin and Calcium Chloride on Assay, Stability, and Recovery of Factor VIII

Abstract: The influence of heparin alone or in conjunction with calcium chloride on the coagulation assay for factor VIII, on the stability of factor VIII in blood and in plasma, and on the recovery of factor VIII in cryoprecipitate and in an intermediate purity concentrate was investigated. A stabilizing effect of heparin and calcium on factor VIII activity in blood and plasma could be confirmed. We were, however, unable to make use of the higher activity that can, under certain circumstances, be recovered in the cryop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…These results have been substantiated by others [4,5]. We [2] and Morgenthaler et al [4] have also found that heparin, added to citrate plasma or when used as a pri mary anticoagulant, significantly stabilizes FVIII so that a two-phase decay does not occur.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…These results have been substantiated by others [4,5]. We [2] and Morgenthaler et al [4] have also found that heparin, added to citrate plasma or when used as a pri mary anticoagulant, significantly stabilizes FVIII so that a two-phase decay does not occur.…”
supporting
confidence: 68%
“…We have previously reported that the FVIII level is considerably higher in heparinized plasma rather than citrated plasma with average values of 1.3 U/ml in heparin compared to 1.0 U/ml in citrate [2,3]. These results have been substantiated by others [4,5]. We [2] and Morgenthaler et al [4] have also found that heparin, added to citrate plasma or when used as a pri mary anticoagulant, significantly stabilizes FVIII so that a two-phase decay does not occur.…”
supporting
confidence: 61%
“…This has important implications in the provision of plasma for large-scale production of factor VIII concentrates. How ever, in view of the initially disappointing results for bulk fractionation of heparinised plasma [8], large-scale stud ies will be required before a recommendation on the use of 0.5 CPD.A2 can be made.…”
Section: Red Cell Preparationsmentioning
confidence: 99%
“…However, in view of the disappointing results for bulk fractionation of hepa rinized plasma [17], similar large-scale studies will be required prior to any recommendation on the use of half-strength citrate anticoagulant. Recent studies on the fractionation of machine plasmapheresis plasma [46,47], containing around 16 mA/citrate, are encouraging.…”
Section: Platelet Concentratesmentioning
confidence: 99%